2021
DOI: 10.3389/fbioe.2021.615218
|View full text |Cite
|
Sign up to set email alerts
|

All-Polymer Printed Low-Cost Regenerative Nerve Cuff Electrodes

Abstract: Neural regeneration after lesions is still limited by several factors and new technologies are developed to address this issue. Here, we present and test in animal models a new regenerative nerve cuff electrode (RnCE). It is based on a novel low-cost fabrication strategy, called “Print and Shrink”, which combines the inkjet printing of a conducting polymer with a heat-shrinkable polymer substrate for the development of a bioelectronic interface. This method allows to produce miniaturized regenerative cuff elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Flexibility also allows for the development of nonplanar device geometries for various applications. Ferrari et al combined ink jet printing of PEDOT:PSS with a heat-shrinkable polymer substrate to form cuff electrodes for nerve regeneration applications . The device was able to stimulate regenerated motor axons to induce a muscular response 3 months after implantation.…”
Section: Flexible and Stretchable Stimulating Electrodesmentioning
confidence: 67%
See 1 more Smart Citation
“…Flexibility also allows for the development of nonplanar device geometries for various applications. Ferrari et al combined ink jet printing of PEDOT:PSS with a heat-shrinkable polymer substrate to form cuff electrodes for nerve regeneration applications . The device was able to stimulate regenerated motor axons to induce a muscular response 3 months after implantation.…”
Section: Flexible and Stretchable Stimulating Electrodesmentioning
confidence: 67%
“…Ferrari et al combined ink jet printing of PEDOT:PSS with a heat-shrinkable polymer substrate to form cuff electrodes for nerve regeneration applications. 141 The device was able to stimulate regenerated motor axons to induce a muscular response 3 months after implantation. In another approach, Tian et al used the flexibility of their parylene C–PEDOT:PSS microelectrodes to create a flexible tubular electrode with drug delivery capability.…”
Section: Flexible and Stretchable Stimulating Electrodesmentioning
confidence: 99%
“…This innovative approach has facilitated long-term implantation throughout the entire lifespan of a mouse, with no discernable tissue damage [112] (figure 4(b)). Inkjet printers can directly pattern polymer substrates into neural regeneration cuff electrodes with PEDOT: PSS and heat-shrinkable polymers to regenerate motor axons and incite muscle responses three months postimplantation [116]. A miniaturized, wireless, and bioresorbable electrotherapy system has been demonstrated to effectively accelerate wound closure, particularly in chronic cases associated with diabetes, by guiding epithelial migration, modulating inflammation, and promoting vasculogenesis, offering a practical solution for electrical stimulation therapy [6].…”
Section: Flexible and Stretchable Interfacementioning
confidence: 99%
“…In rat models of chronic and acute nerve injury, the fabricated RnCE has been shown to heal sciatic nerve injuries. However, the unique regenerative PNI microelectrode sequence showed that the long-term implantation of this electrode could be harmful [ 104 ].…”
Section: Application Of Decm-derived Bioinks In 3d Bioprintingmentioning
confidence: 99%